Patient-derived tumor xenograft strategies for informed management of patients with metastatic melanoma. Issue 3 (June 2016) - Qassemyar, Ahmad; Gabert, Pierre-Elliott; Kluza, Jerome; Duquennoy-Martinot, Véronique; Mortier, Laurent; Marchetti, Philippe; Guerreschi, Pierre
Abstract : Metastatic melanoma has benefited from immunotherapy and targeted therapy advances. Faced with the inescapable onset of treatment resistance, the choice of a second-line treatment can be guided by a patient-derived tumor xenograft (PDTX). This new approach requires an excellent multidisciplinary collaboration where the surgeon has a key role to play. Each patient included (stage IIIC or IV) presented with subcutaneous melanoma metastasis that could be surgically resected. The surgeon performed orthotopic PDTX on CB17-SCID mice. To validate the model, tumor material was amplified over three successive generations of animals to obtain cohorts compatible with carrying out a study to compare treatment response by targeted therapy (vemurafenib versus controls). Tumors were characterized (histologically and genetically) at all stages of the generations' amplification. Functional imaging by fluorine-18 fluorodeoxyglucose PET scan was performed for the third generation PDTX. Seventeen patients with a mutated BRAF V600E subcutaneous metastasis were included, yielding 257 PDTX. Clinical, histological, and genetic characteristics of the grafted tumors were stable over the three mice generations. The treatment response to vemurafenib was observed for all PDTX. The fluorine-18 fluorodeoxyglucose PET scan evidenced a decreased in glucose uptake in the treated tumors. PDTX models are being widely used in fundamental research and are more compatible with clinical issues. If PDTX are simple and easily reproducible in metastatic melanoma, an organized multidisciplinary platform is essential to implement them. In our experience, surgeons have a key role to play in the cohesion of this new therapeutic approach.